Besedilna matrica in struktura vzorca besedila problem - rešitev ter možnost njune uporabe pri analizi besedil v šolski praksi - Starc, Sonja (Jezik in slovstvo, 2006)
The article gives an insight into the structure of text, as theoretically founded by Michael Hoey, which is also applied to some Slovene examples. Following the analysis of high school final Matura exams in Slovene as a Second Language, the author aims to establish possible ways of using a textual matrix and a schematic illustration of the problem-solution text type in schools when testing textual balance, demonstrating an interdependent relation between the text type intended for achieving a goal, i.e. instructions, and the realisation of the problem-solution text type.
Keywords: besedila; didactic method; didaktika; eseji; linguistics; lingvistika; matura; tekstna lingvistika